UDIDAYA TANAMAN JAGUNG (Zea mays) DENGAN APLIKASI RHIZOBAKTERI DI NAGARI SUNGAI DURIAN KABUPATEN SOLOK - Yulmira Yanti; Munzir Busniah; Zulfadly Syarif; Intan Sari Pasaribu (Jurnal Pengabdian Warta Andalas, 2018)
Nagari Sungai Durian of Solok District is one of the village that has various problems suchas drought, high number of unused land and the distance of urban access. In the cultivation of foodcrops required a lot of water such as rice, so that productivity is not optimal. For that the selection ofcorn as a cultivation plant is a possible thing because corn plants merupkan food crops that do notrequire much water. But some of the constraints faced when corn plant perspectives are low productivitydue to disruption of pests and diseases and soil less fertile. The solution that can be offered is by plantingcorn crops that are more resistant to drought and the use of rhizobacteria as pest and disease controlagents. In addition to pest and disease control agents, the use of rhizobacteria which also called PGPR(Plant Growth Promoting Rhizobacteria) that can increase growth and yield of plants. The purpose ofthis community service program is to provide knowledge to the community in the cultivation of corncrops with the application of rhizobacteria. This activity is done by socialization and demonstrationplot. This activity has been able to educate the general community about farmers about corn cultivationwith rhizobakteri application. From this activity also can be concluded that corn plant with applicationof Rhizobakteri have growth and yield higher than corn plant without application of Rhizobakteri.